Analisis Kinerja Karyawan Room Boy Pada Departemen Housekeeping Di Crystal Lotus Hotel Yogyakarta - Budi Tiyo Warmadi; Samsul Arifin (EBBANK, 2023)
This study focuses on the analysis of Room Boy employees’ performance in the Housekeeping department at Crystal Lotus Hotel Yogyakarta. The purpose of this study is to determine the performance of Room Boy at Crystal Lotus Hotel. The data collection approach involves qualitative techniques to obtain the required data. The researcher gathered information by using observations, interviews, and documentation to produce a result. Then, based on the results and discussion below, the performance quality of Crystal Lotus Hotel Room Boy employees is pretty poor. The primary issues creating negative replies are the lack of cleanliness and attractiveness in hotel guest rooms, as well as the comfort of visitors who are not guaranteed. The findings of this study are discussed in depth in the discussion section, including references to expert theories. The results obtained through interviews showed that Room Boy employees at the Crystal Lotus Hotel were said to be in the unfavorable category and needed to be improved as stated by the source directly and the results of the processed data obtained by the researchers. Based on the results of observations and documentation obtained through guest comments, from the five performance indicators according to Robbin, the performance of Room Boy employees at the Crystal Lotus Hotel only met the indicators of quality and punctuality, but was fulfilled in the sufficient category. While the other three indicators, which are the quantity of work, effectiveness, and independence are still not fulfilled. Then, as well as the results obtained through the questionnaire, it shows that the quality of performance and timeliness of Room Boy Crystal Lotus Hotel employees is quite good. However, the other three indicators are still not met. Based on the results of the analysis above from the data obtained, there are several reasons why the performance of Room Boy employees in the Housekeeping department at the Crystal Lotus Hotel is considered not good which includes a lack of knowledge, skills and abilities.